Research of changes hydro-puller device internal cavitie’s geometry for order to improve the thermal state - Novikov V.I. (Научно-технический вестник Брянского государственного университета)
Research of changes hydro-puller device internal cavitie’s geometry for order to improve the thermal state The paper is devoted to the study of the influence on changes in their thermal balance during operation by improving the cooling conditions of sections of the drill shaft with contact surfaces of changes in geometric characteristics, such as diameter and length, of the internal cavity for supplying working fluid in high-pressure hydro-puller device for hydro-jet technologies. The axisymmetric simulation not on a full-size transmit-ting device was carried out, but on one-eighth part in order to reduce the time of both creating the model itself and the amount of calculations. A model created in the computing environment «Ansys» with a computational grid for calculating equivalent stresses is shown. The stress distributions calculated by the finite element method for various combinations of the geometry of the transfer device revealed the corresponding boundaries for the rational change in the diameter and length of the internal cavity, allowing to ensure its operability of the structural unit in combination with maximum cooling of the most thermally loaded sections of the shaft. Dimensionless geometric parameters (reduced diameter and reduced length of the internal cavity) are introduced for a general description of the geometry of transmitting devices for hydro-jet technologies. Graphs of the dependences of voltage values on the given values were obtained.